Advokasi Masyarakat terhadap Klaim Kepemilikan Tanah oleh Korporasi: (Studi Kasus di Pulau Pari, Kepulauan Seribu) - Abdul Rahman Hamid; Abdul Aziz Tambunan; Martini Anwar; Annisa Rahmi Faisal (FKIP, Universitas Palangka Raya, 2026)
This community service activity was carried out to strengthen the advocacy capacity of the Pari Island community, Seribu Islands, DKI Jakarta, in defending their rights to land and living space from corporate claims of control. The problems faced by the community are not only related to land disputes, but also include social pressure, community polarization, threats of eviction, economic weakening, and damage to coastal ecosystems due to reclamation activities. The community service activity was carried out through participatory dialogue, problem mapping, strengthening legal literacy, discussions on advocacy strategies, and the formulation of a sustainable assistance model with the community. The results of the activity indicate that the Pari Island community has carried out various forms of advocacy, including collective action, collaboration with civil society organizations, media publications, legal assistance, institutional complaints, and environmental advocacy. However, this advocacy still needs to be strengthened through internal consolidation, documentation of intimidation, strengthening the community economy, mangrove protection, and strengthening the community's mental health. This article offers the concept of advocacy for living space resilience as a model for assisting small island communities. This model combines legal, social, media, environmental, economic, psychological, and community-based documentation advocacy. With this approach, community service serves not only as an outreach activity but also as a socio-legal assistance process that strengthens community resilience in the face of long-term agrarian and ecological conflicts.